PERAN OTORITAS JASA KEUANGAN SEBAGAI LEMBAGA PENGAWASAN DALAM MELINDUNGI NASABAH PENYIMPAN - Benny Krestian Heriawanto (Fakultas Hukum Universitas Islam Malang, 2016)
The weakness of supervision on the field of banking cause weakness of protection for depositors. The weakness of supervision cause amerge of infraction that lost out for depositors. This condition is caused by a large and complex of duty and responsibility oh the Indonesian Bank as the institution of banking supervisor. In order to overcome the problems, ,formed Otoritas Jasa Keuangan that replace the role of Indonesian Bank on the supervision of banks in order to protect its depositor as set out in Undang-undang Nomor 21 Tahun 2011 tentang Otoritas Jasa Keuangan. It is known that there are differences in the role of the supervision of Indonesian bank compared to Otoritas Jasa Keuangan gainst the banking especially in order to protect its depositors, and also know that Undang-undang Nomor 21 Tahun 2011 tentang Otoritas Jasa Keuangan doesn’t meet and demand The BaselCore Principles.Keywords: Otoritas Jasa Keuangan, Protection of Depositor, Supervision.